2010
DOI: 10.1128/jb.01052-09
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of IntDOT

Abstract: CTnDOT integrase (IntDOT) is a member of the tyrosine family of site-specific DNA recombinases. IntDOT is unusual in that it catalyzes recombination between nonidentical sequences. Previous mutational analyses centered on mutants with substitutions of conserved residues in the catalytic (CAT) domain or residues predicted by homology modeling to be close to DNA in the core-binding (CB) domain. That work suggested that a conserved active-site residue (Arg I) of the CAT domain is missing and that some residues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…coli in vivo integration and in vitro assays. In vivo integration and DNA binding and ligation assays were performed as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…coli in vivo integration and in vitro assays. In vivo integration and DNA binding and ligation assays were performed as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
“…Recent in vitro experiments and homology modeling indicated that R285 might provide the function of the missing arginine (8,12). This arginine residue was predicted to project into the active site, where it could participate in catalysis.…”
Section: Resolution Of Holliday Junctions By Wild-type Intdot Sincementioning
confidence: 99%
See 3 more Smart Citations